Productivity modelling of a developed inclined stepped solar still system based on actual performance and using a cascaded forward neural network model. (1st January 2018) - Abujazar, Mohammed Shadi S.; Fatihah, Suja; Ibrahim, Ibrahim Anwar; Kabeel, A.E.; Sharil, Suraya
Abstract: This paper presents a cascaded forward neural network model for predicting the productivity of a developed inclined stepped solar still system. The actual recorded data of the developed inclined stepped solar still system is used to develop the proposed model. The results of the predicted productivity are compared with that obtained from regression and linear models. In this study, three statistical error terms are used to evaluate the proposed model: root mean square error (RMSE), mean absolute percentage error (MAPE) and mean bias error (MBE). The results show that the proposedcascaded forward neural network (CFNN) model more accurately predicts the productivity of the system than the other modelsmentioned. The RMSE, MAPE and MBE values of the proposed model are 22.48%, 18.51% and −26.46%, respectively. Therefore, the CFNN model provides benefits for modelling the solar still. Highlights: The performance of the stepped solar still using a cascaded forward neural network is presented. The effect of environmental parameters on the productivity of the system is studied. In this study, three statistical error terms are used to evaluate the proposed model. The RMSE, MAPE and MBE values of the proposed model are 22.48%, 18.51% and −26.46%, respectively.